Overexpression of Cinnamoyl-CoA Reductase 2 in Brassica napus Increases Resistance to Sclerotinia sclerotiorum by Affecting Lignin Biosynthesis - Liu, Dongxiao; Wu, Jian; Lin, Li; Li, Panpan; Li, Saifen; Wang, Yue; Li, Jian; Sun, Qinfu; Liang, Jiansheng; Wang, Youping (Frontiers in Plant Science, 2021)
Sclerotinia sclerotiorum causes severe yield and economic losses for many crop and vegetable species, especially Brassica napus. To date, no immune B. napus germplasm has been identiﬁed, giving rise to a major challenge in the breeding of Sclerotinia resistance. In the present study, we found that, compared with a Sclerotinia-susceptible line (J902), a Sclerotinia-resistant line (J964) had better xylem development and a higher lignin content in the stems, which may limit the invasion and spread of S. sclerotiorum during the early infection period. In addition, genes involved in lignin biosynthesis were induced under S. sclerotiorum infection in both lines, indicating that lignin was deposited proactively in infected tissues. We then overexpressed BnaC.CCR2.b, which encodes the first rate-limiting enzyme (cinnamoyl-CoA reductase) that catalyzes the reaction of lignin-specific pathways, and found that overexpression of BnaC.CCR2.b increased the lignin content in the stems of B. napus by 2.28%-2.76% under normal growth conditions. We further evaluated the Sclerotinia resistance of BnaC.CCR2.b overexpression lines at the flower-termination stage and found that the disease lesions on the stems of plants in the T2 and T3 generations decreased by 12.2%-33.7% and 32.5%-37.3% compared to non-transgenic control plants, respectively, at 7 days post-inoculation (dpi). The above results indicate that overexpression of BnaC.CCR2.b leads to an increase in lignin content in the stems, which subsequently leads to increased resistance to S. sclerotiorum. This study provides a new avenue for regulating the synthesis of lignin via genetic engineering. Our ﬁndings demonstrate that increasing the lignin content in the stems of B. napus is an important strategy for controlling Sclerotinia.